The Role of Teachers’ Experiential Learning and Reflection for Enhanching their Autonomous Personal and Professional Development - Adi Suryani; Tri Widyastuti (JURNAL SOSIAL HUMANIORA (JSH), 2015)
Today’s teachers are not only teaching, but they have to fulfill various educational roles. This situation demands teachers to learn continuously. They should develop themselves to improve students’ achievement. To grow continuously, teachers should not just wait for formal, instructed or top-down training or learning. They should be autonomous and self directed. They should be aware and analyze what they need and how they should obtain knowledge or skill that they need. Autonomous teachers learn by reflecting their daily teaching and learning experiences. They use their experience as opportunity to learn. There are three main sources of teachers’ learning: their teaching experiences, sharing ideas in professional communities, and by researching.